2007
DOI: 10.2337/dc06-2052
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Effects of Type 2 Diabetes on Brain Tissue Volumes and Cerebral Vasoreactivity

Abstract: OBJECTIVE -The aim of this study was to evaluate the regional effects of type 2 diabetes and associated conditions on cerebral tissue volumes and cerebral blood flow (CBF) regulation.RESEARCH DESIGN AND METHODS -CBF was examined in 26 diabetic (aged 61.6 Ϯ 6.6 years) and 25 control (aged 60.4 Ϯ 8.6 years) subjects using continuous arterial spin labeling (CASL) imaging during baseline, hyperventilation, and CO 2 rebreathing. Regional gray and white matter, cerebrospinal fluid (CSF), and white matter hyperintens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
208
3
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(229 citation statements)
references
References 40 publications
13
208
3
5
Order By: Relevance
“…Our result expands previous observations from Doppler (Groschel et al, 2007) and ASL (Last et al, 2007) studies, where decreased response to hypercapnia was found in association with vascular risk factors. Specifically, among all the subjects, both hippocampal and global cortical VR h were affected by vascular risk, corroborating the contribution of impaired vessel function to the damage of brain regions strategic for cognition.…”
Section: Discussionsupporting
confidence: 80%
“…Our result expands previous observations from Doppler (Groschel et al, 2007) and ASL (Last et al, 2007) studies, where decreased response to hypercapnia was found in association with vascular risk factors. Specifically, among all the subjects, both hippocampal and global cortical VR h were affected by vascular risk, corroborating the contribution of impaired vessel function to the damage of brain regions strategic for cognition.…”
Section: Discussionsupporting
confidence: 80%
“…One study reported that patients with diabetic retinopathy, a complication of type 1 diabetes, showed reduced gray matter density in the inferior frontal gyrus and right occipital lobe when compared patients without retinopathy (35). Patients with type 2 diabetes also had 3% less gray matter and ∼17% increase in CSF in the parieto-occipital region (36).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in patients with type 2 diabetes, regional white matter hyperintensities were associated with reduced cerebrovascular CO 2 responsiveness. 43 Despite the relatively small sample size, further limited by missing NIRS data in 9 patients and 3 controls, the strongly significant decreases in cerebrovascular CO 2 responsiveness in the SCD patients suggest an important role for impaired cerebrovascular CO 2 responsiveness in the increased susceptibility to stroke in SCD, regardless of the presence or absence of silent cerebral infarcts. However, whether silent cerebral infarcts are related to cerebrovascular CO 2 responsiveness, needs to be elucidated in a larger study with cerebrovascular CO 2 responsiveness measurements combined with cerebral MRI.…”
Section: Discussionmentioning
confidence: 99%